TEN COMMONLY AVAILABLE MEDICINAL PLANTS IN MALAYSIA USED FOR THE TREATMENT OF DIABETES – A REVIEW - Sekar, Mahendran; Abdullah, Muhammad Zulhilmi bin; Azlan, Ahmad Yasser Hamdi bin Nor; Nasir, Siti Nabila binti; Zakaria, Zahida binti; Abdullah, Mohd Syafiq bin (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Diabetes mellitus is a common and serious metabolic disorder throughout the world. Search for newer drugs continues because the existing synthetic drugs have several limitations and side effects. Traditional plants have been used throughout the world for the treatment of diabetes. Objective: The present study is an attempt to list of the commonly available medicinal plants with antidiabetic and related beneficial effects originating from different parts of Malaysia. Method: This study was carried out for a general knowledge in which to give information on common medicinal plants in Malaysia used for the treatment of diabetes. Results: There are 10 such very commonly available medicinal plants were found and described in this review which clearly shows the importance of herbal plants in the treatment of diabetes. Conclusion: Only a few plants have been subjected to detailed scientific investigation. However, further pharmacological and toxicological studies at the molecular and clinical levels are still warranted to confirm the potential of these plants. Keywords: Medicinal plants, Malaysia, Diabetes